Надфасціальна перфорантотомія у комплексному лікуванні хворих з трофічними виразками нижніх кінцівок венозного генезу - Сироїд, М.В.; Гурський, Р.В.; Войтановський, І.М.; Титюк, В.А.; Сливка, В.І. (Таврический медико-биологический вестник, 2011)
Представлен опыт оперативного лечения 3681 больных с различными формами и степенями ХВН за период с 1993 по 2010 годы. The article presented the experience of operative treatment of 3891 patients with various forms and degrees of chronic venous insufficiency (CVI) for the period from 1993 to 2010.